Exploring culture and tourism of Ternate Island, a prominent sultanate in eastern Indonesia : A Report - Meranggi, Yogi (Bali Tourism Journal, 2024)
Ternate is a city situated at the foot of the Gamalama volcano on Ternate Island in the province of North Maluku. Historically, Ternate has served as a centre of civilization for nearly all the communities in North Maluku. Its cultural landscape reflects a complex blend of historical legacies, indigenous traditions, and external influences. As a significant centre of civilization, Ternate's historical importance stems from its role in the spice trade and as the seat of the influential Sultanate. Established in the 13th century, the Sultanate merged local customs with Islamic principles, shaping its governance structures, social hierarchy, and religious practices. Despite the Islamization process, Ternate's social fabric retained a diverse ethos, with indigenous beliefs coexisting alongside Islam, reflecting a multifaceted cultural landscape. This intricate social structure is evident in Ternate's hierarchical society, where noble families interact with commoners within a structured framework, upholding ancestral traditions. Ritual practices like the kololi kie and fere kie highlight the islanders' deep reverence for their cultural roots, emphasizing a solid connection to sacred sites and ancestral spirits, reinforcing the enduring importance of tradition in shaping Ternate's collective identity. Beyond its cultural heritage, Ternate's appeal lies in its diverse natural landscape, offering a range of geographical features and scenic views. From the majestic Mount Gamalama to the serene Ngade Lake, Ternate boasts various natural attractions for exploration and admiration. Additionally, historical landmarks such as Kalamata Fort and Sultan Ternate Mosque provide insights into the island's colonial history and Islamic heritage, enriching visitors' cultural experiences.